Bisulfite-free direct detection of 5-methylcytosine and 5-hydroxymethylcytosine at base resolution - Liu, Y; Siejka-Zielinska, P; Velikova, G; Bi, Y; Yuan, F; Tomkova, M; Bai, C; Chen, L; Schuster-Boeckler, B; Song, C (Springer Nature, 2019)
Bisulfite sequencing has been the gold standard for mapping DNA modifications including 5-methylcytosine (5mC) and 5-hydroxymethylcytosine (5hmC) for decades1,2,3,4. However, this harsh chemical treatment degrades the majority of the DNA and generates sequencing libraries with low complexity2,5,6. Here, we present a bisulfite-free and base-level-resolution sequencing method, TET-assisted pyridine borane sequencing (TAPS), for detection of 5mC and 5hmC. TAPS combines ten-eleven translocation (TET) oxidation of 5mC and 5hmC to 5-carboxylcytosine (5caC) with pyridine borane reduction of 5caC to dihydrouracil (DHU). Subsequent PCR converts DHU to thymine, enabling a C-to-T transition of 5mC and 5hmC. TAPS detects modifications directly with high sensitivity and specificity, without affecting unmodified cytosines. This method is nondestructive, preserving DNA fragments over 10 kilobases long. We applied TAPS to the whole-genome mapping of 5mC and 5hmC in mouse embryonic stem cells and show that, compared with bisulfite sequencing, TAPS results in higher mapping rates, more even coverage and lower sequencing costs, thus enabling higher quality, more comprehensive and cheaper methylome analyses.